A polymeric europium complex with the ligand thiophene-2-carboxylic acid: Synthesis, structural and spectroscopic characterization - Cagnin, Flavia [UNESP]; Davolos, Marian Rosaly [UNESP]; Castellano, Eduardo E. (Elsevier, 2014)
A polymeric complex [Eu(α-tpc)3(α-Htpc) 2]n and its characterization by single crystal X-ray and thermal analysis, infrared and photoluminescence spectroscopies are described. The compound crystallizes in the monoclinic Cc space group. The asymmetric unit is formed from a europium ion bonded to one carboxyl oxygen of five different thiophene carboxylic moieties. Three of these moieties are deprotonated and bridge between neighboring europium ions giving rise to an infinite polymer along the c axis. Besides the europium characteristic emission lines, the emission spectra show unambiguously the crystal size effect on the 5D0 → 7F0 transition. The complex thermal decomposition at 220 C leads to a stable luminescent complex in which the 5D0 → 7F4 transition reveals a monomeric characteristic. The Judd-Ofelt intensity parameters to the polymeric and the monomeric compound with the same ligand and coordination number were compared. © 2013 Published by Elsevier Ltd.
Keywords: FTIR spectroscopy; Photoluminescence spectroscopy; Thermal analysis; X-ray diffractometry